Lifestyle and Non-Communicable Diseases: A double edged sword for future India - Chakma, Joy Kumar; Gupta, Sanjay (Indian Journal of Community Health, 2014)
Lifestyle has long been associated with the development of many chronic diseases. WHO has recognized diabetes, cardiovascular disease and stroke, cancer and chronic lung disease/COPD as major non-communicable diseases (NCDs). These major NCDs share common lifestyle related risk factors like physical inactivity, unhealthy diet, tobacco use and harmful use of alcohol. Globally, the current scenario of NCDs is the major cause of morbidity and mortality. According to WHO Report 2004, they account for almost 60% of deaths and 47% of global burden of disease. Epidemics of NCDs are presently emerging or accelerating in most developing countries. In India, 53% of the deaths in 2008 were due to NCDs (WHO) and cardiovascular disease (CVDs) alone account for 24 percent of all deaths. As of 2005, India experienced the “highest loss in potentially productive years of life” worldwide and the leading cause of death was cardiovascular disease; mostly affecting people aged 35-64 years. The projected cumulative loss of national income for India due to NCDs mortality for 2006-2015 will be USD237 billion. By 2030, this productivity loss is expected to double to 17.9 million years lost. These major NCDs are largely preventable through effective interventions by tackling the lifestyle related modifiable risk factors. This review discusses the current scenario of NCDs with their impact on health and socioeconomic development, the threat posed by the rising trends of disease burden along with socio-demographic transition and the challenges needs to be addressed for the prevention and control of NCDs.